PELATIHAN ASESMEN BERDASARKAN KURIKULUM MERDEKA SEBAGAI WUJUD PENGUATAN SDM SEKOLAH PENGGERAK DALAM PEMBELAJARAN ABAD 21 - Arna Putri, Gusti Ayu Made; NOVIANTARI, PUTU SUARNITI; NOVIYANTI, PUTU LEDYARI; LUQMAN, NAJWA RIZQI; PUSPITA, NI PUTU DHILA; SEPTYA DEWI, NI MADE WIDYA (Bestari: Jurnal Pengabdian Kepada Masyarakat, 2024)
Abstract: This community service activity aims to determine the level of understanding of participants before and after assessment training based on the independent curriculum as a form of strengthening human resources in the propulsion school. The community service activities were carried out at Dwijendra Bualu Middle School on July 6, 2023. Dwijendra Bualu Middle School became an inspirational propulsion school starting 2022. Assessment training based on the independent curriculum was filled by presenters with two related topics, such as differentiated learning assessment and a project to strengthen the profile of Pancasila students (P5). Participants who took part in the training were 10 people from all teachers at SMP Dwijendra Bualu. Before the training begins, participants are given a pre-test to find out the level of understanding of the assessment based on the independent curriculum. Then at the end of the activity, participants were also given a post-test to find out the increment on understanding of the assessment based on the independent curriculum presented by the resource persons. There were 8 questions given to participants using the Wordwall application. In the beginning pre-test results, participants' understanding of the assessment based on the independent curriculum was 70% and the post-test results were 85% after training given. Based on these results, concluded that an increment occurred in participants’ level of understanding after assessment training based on the independent curriculum as a form of strengthening human resources in propulsion school by 21,4%. Keywords : assessment, independent curriculum, propulsion school Abstrak: Kegiatan pengabdian kepada masyarakat ini bertujuan untuk mengetahui tingkat pemahaman peserta sebelum dan sesudah diberikan pelatihan asesmen berdasarkan kurikulum merdeka sebagai wujud penguatan SDM di sekolah penggerak. Kegiatan pengabdian dilaksanakan di SMP Dwijendra Bualu pada tanggal 6 Juli 2023. SMP Dwijendra Bualu menjadi sekolah penggerak terinspiratif dimulai pada tahun 2022. Pelatihan asesmen berdasarkan kurikulus merdeka diisi oleh pemateri dengan dua topik yang terkait yaitu asesmen pembelajaran berdiferensiasi dan proyek penguatan profil pelajar pancasila (P5). Adapun peserta yang mengikuti pelatihan tersebut berjumlah 10 orang dari semua guru di SMP Dwijendra Bualu. Sebelum pelatihan dimulai peserta diberikan pre-test untuk mengetahui sejauh mana tingkat pemahaman asesmen berdasarkan kurikulum merdeka. Kemudian pada akhir kegiatan peserta kembali diberikan post-tes untuk mengetahui peningkatan pemahaman asesmen berdasarkan kurikulum merdeka yang dipaparkan oleh narasumber. Pertanyaan yang diberikan kepada peserta berjumlah 8 soal dengan menggunakan aplikasi Wordwall. Pada hasil pre-test yang diberikan diawal diperoleh tingkat pemahaman peserta terhadap asesmen berdasarkan kurikulum merdeka sebesar 70% dan setelah diberikan pelatihan diperoleh hasil pos-test sebesar 85%. Berdasarkan hasil tersebut dapat disimpulkan bahwa terjadi peningkatan pemahaman peserta sesudah diberikan pelatihan asesmen berdasarkan kurikulum merdeka sebagai wujud penguatan SDM di sekolah penggerak sebesar 21,4%. Kata Kunci: asesmen, kurikulum merdeka, sekolah penggerak